Separate and dissenting opinions: their role in the practice of the ICJ - Logacheva, Ellina (Riga Graduate School of Law, 2019)
The purpose of the thesis is to draw attention to the significance of the individual opinions in the practice of the International Court of Justice. The author aims to define the actual role of individual opinions in the system of work of the International Court of Justice by means of analyses of individual opinions appended to the Court’s judgements, rendered under contentious and advisory jurisdiction of the Court. In this thesis possible solutions proposed of how the existence of individual opinions should be regulated in the basic documents of the International Court of Justice.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; International Court of Justice